A multifunctional ruthenium based dye for hybrid nanocrystalline titanium dioxide/poly(3-hexylthiophene) solar cells - Pirashanthan, A.; Murugathas, T.; Mariappan, K.; Ravirajan, P.; Velauthapillai, D.; Yohi, S. (University of Jaffna, 2020)
This work reports the influence of a Ru based dye (RuC) on enhancing the performance of nanocrystalline titanium dioxide (TiO2)/Poly(3-hexylthiophene) (P3HT) solar cells. UV–Vis absorption spectra of TiO2/ P3HT and TiO2/RuC/P3HT films reveal that the absorption spectrum of TiO2/P3HT is broadened in the UV region due to the addition of the RuC dye. With pumping laser at the wavelength corresponds to max imum absorption of P3HT, photoluminescence (PL) of TiO2/RuC/P3HT nanocomposite film was signifi cantly quenched in comparison with PL of TiO2/P3HT film which confirms the efficient exciton dissociation in TiO2/RuC/P3HT. The insertion of the dye suppresses the dark current by two orders of magnitude in the cells while extends external quantum efficiency (EQE) spectra and hence increases the average short circuit current density (JSC) from 2.52 (±0.25) to 6.44 (±0.43) mA/cm 2 , resulting in three fold power conversion efficiency (PCE) increment from 0.73 (±0.06) to 2.35 (±0.13) %, under 100 mW cm 1 (1 sun) illumination with AM 1.5 filter.
Keywords: Solar cell; Titanium dioxide; Poly(3-hexylthiophene); Co-sensitizers